Lontar Rsi Sasana Catur Yuga: Suatu Tinjauan Wacana Kritis - Ida Ayu Dewi Astuti (Udayana University, 2026)
Rsi Sasana Catur Yuga text contains rules of conduct for a priest during a specific time period (Satya-kaliyuga). Priests in Bali are also called Sulinggih. Advances in technology have significantly influenced the position of the Sulinggih in maintaining personal purity. Research conducted through critical discourse analysis using a qualitative approach found that the values ​​of the Rsi Sasana Catur Yuga are still relevant and widely used, implemented as a guideline for Sulinggih behavior, and proper application of these teachings has implications for the formation of ethical and characterful Sulinggih.